1953
DOI: 10.1079/bjn19530017
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Calcium Retention and Body Stores of Calcium in the Rat: Effect of Age and of Vitamin D

Abstract: It is known that the rate of calcium absorption decreases with progressive calcification of the skeleton (see e.g. Fairbanks

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…Because bone undergoes continuous remodeling, there is an opportunity for periods of inadequacy to be resolved. For example, deficits in dietary calcium were reversed with calcium repletion or time (21–23) . In our study, the early disadvantages of adequate calcium CaCO 3 compared with that from NFDM largely resolved with age.…”
Section: Discussionmentioning
confidence: 48%
“…Because bone undergoes continuous remodeling, there is an opportunity for periods of inadequacy to be resolved. For example, deficits in dietary calcium were reversed with calcium repletion or time (21–23) . In our study, the early disadvantages of adequate calcium CaCO 3 compared with that from NFDM largely resolved with age.…”
Section: Discussionmentioning
confidence: 48%
“…Henry and Kon (8) have already demonstrated that although bone mineralization depends on the calcium content of the diet during the growth period, calcification becomes normal at 1 year of age regard less of the dietary calcium level.…”
mentioning
confidence: 99%
“…The subject of calcium (Ca) absorption, re tention and bone metabolism in aging is of interest not only from a gerontological view point but also because of its possible role in the pathogenesis of osteoporosis, essentially a condition of aging, probably multi factorial in nature [Albanese, 1977], It is likely that poor or decreased absorption and retention of Ca may contribute to the progressive loss of bone during senescence. The absorption of Ca has been reported to be less in mature than in growing animals [Henry and Kon, 1953;Hansard and Crowder, 1957;Milhaud et al, 1963] and humans [Canniggia et al, 1964[Canniggia et al, /1965Bullarnore ex al., 1970;Dequeker, 1975]. Or, if no aging effect on Ca absorp tion was detected, it was noted that the older animal was less able to adapt to decreased dietary Ca intake than younger ones [Henry et al, 1960;Draper, 1964].…”
mentioning
confidence: 99%